Environmental Audits and Third Party Certification of Management Practices: Firms' Motives, Audit Orientations, and Satisfaction with Certification. Issue 2 (July 2016) - Prajogo, Daniel; Castka, Pavel; Yiu, Daphne; Yeung, Andy C.L.; Lai, Kee‐Hung
Abstract : In this study, we investigate the interplay between motives for certification, audit orientations and firms' benefits and satisfaction with ISO 14001 certification. We demonstrate that firms' motive for certification is an important determinant in firms' satisfaction. Firms with internal motivations (such as improvements in their environmental performance) require audits that foster continuous improvement and tend to report greater benefits and satisfaction with the third party certification compared to those that are driven by external motives (such as to match competitors' actions). Our findings show that only an improvement orientation towards auditing would lead to clients' satisfaction with ISO 14001. In contrast, external motives for pursuing ISO 14001 certification make firms less focused on environmental improvement through the standard, and, thus, less satisfied with the certification. Our research demonstrates how different motives for seeking certification lead to different satisfaction levels with voluntary standards in an environmental management context.